Pengembangan Aplikasi Transaksi Penjualan Berbasis Visual Programming untuk Meningkatkan Efisiensi dan Pembelajaran - Pratama, Muhammad Aji Yoga; Bagus, Ahmad Dhaby S.; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
Sales transaction applications are a solution commonly used in the business world to simplify the process of recording and managing transactions. In the context of a visual programming course, this application serves as a learning tool for applying programming concepts based on an interactive graphical interface. This article discusses the development of sales transaction applications using visual programming languages, focusing on the use of graphical components such as input forms, data tables, and action buttons. Users can perform various activities, including entering item data, recording sales, calculating total prices, and generating transaction reports. The application development process includes interface design, transaction logic processing, and the implementation of a data storage system. The results of this application help students understand workflows in creating desktop-based software and deepen their understanding of basic visual programming concepts involving user interfaces and system interactions.